Eficacia de agentes desensibilizantes nitrato de potasio, fluoruro de sodio y ácido oxálico post blanqueamiento dental con peróxido de hidrógeno al 35 porciento - Torres Vizcaíno, Fernanda Estefanía (2017)
Today there is a great demand in dental aesthetic procedures the most requested is tooth whitening that in spite of offering high esthetic and excellent results can bring adverse effects such as tooth sensitivity that is often very annoying and even very intolerably for the patient. This is why it is important to perform this study and find the effective desensitizing agent to treat tooth sensitivity immediately and in a permanently way until the pain disappears. Therefore, an investigation was done on 40 patients which were divided into 2 groups; The first group of 20 patients which were applied immediately after application of the bleaching agent 35 percent of hydrogen peroxide, 5 percent of potassium nitrate and 2 percent of sodium fluoride was immediately placed; The second group of 20 patients which were applied immediately after application of the bleaching agent 35 percent of hydrogen peroxide, 3 percent oxalic acid was immediately placed. Sensitivity evaluation was performed by applying a cold air stimulus through the triple syringe on the surfaces of the teeth and was valued by a test that contains a scale of sensitivity in three times after the immediately application of the bleaching agent, after the immediately application of the desensitizing agent, three days after application of desensitizing agent and at 15 days after application of the desensitizing agent. Where it was determined that desensitizing agents 5 percent of potassium nitrate and 2 percent of sodium fluoride reached an efficiency of 100 percent performing an effective desensitizing effect by the immediate and permanent elimination of tooth sensitivity at the end of the treatment, whereas the desensitizing agent 3 percent of oxalic acid reached a percentage of 85 percent of efficiency in the complete elimination of tooth sensitivity however it was moderately effective at 15 percent because its effect was temporary because of factors that affect the action of desensitizing agents such as a high diet in acids or a toothbrush abrasion.